Redefining Cut-Points for High Symptom Burden of the Global Initiative for Chronic Obstructive Lung Disease Classification in 18,577 Patients With Chronic Obstructive Pulmonary Disease - Smid, Dionne E; Franssen, Frits M E; Gonik, Maria; Miravitlles, Marc; Casanova, Ciro; Cosio, Borja G; de Lucas-Ramos, Pilar; Marin, Jose M; Martinez, Cristina; Mir, Isabel; Soriano, Joan B; de Torres, Juan P; et al. (Journal of the American Medical Directors Association, 2017)
BACKGROUND: Patients with chronic obstructive pulmonary disease (COPD) can be classified into groups A/C or B/D based on symptom intensity. Different threshold values for symptom questionnaires can result in misclassification and, in turn, different treatment recommendations. The primary aim was to find the best fitting cut-points for Global initiative for chronic Obstructive Lung Disease (GOLD) symptom measures, with an modified Medical Research Council dyspnea grade of 2 or higher as point of reference. METHODS: After a computerized search, data from 41 cohorts and whose authors agreed to provide data were pooled. COPD studies were eligible for analyses if they included, at least age, sex, postbronchodilator spirometry, modified Medical Research Council, and COPD Assessment Test (CAT) total scores. MAIN OUTCOMES: Receiver operating characteristic curves and the Youden index were used to determine the best calibration threshold for CAT, COPD Clinical Questionnaire, and St. Georges Respiratory Questionnaire total scores. Following, GOLD A/B/C/D frequencies were calculated based on current cut-points and the newly derived cut-points. FINDINGS: A total of 18,577 patients with COPD [72.0% male; mean age: 66.3 years (standard deviation 9.6)] were analyzed. Most patients had a moderate or severe degree of airflow limitation (GOLD spirometric grade 1, 10.9%; grade 2, 46.6%; grade 3, 32.4%; and grade 4, 10.3%). The best calibration threshold for CAT total score was 18 points, for COPD Clinical Questionnaire total score 1.9 points, and for St. Georges Respiratory Questionnaire total score 46.0 points. CONCLUSIONS: The application of these new cut-points would reclassify about one-third of the patients with COPD and, thus, would impact on individual disease management. Further validation in prospective studies of these new values are needed.
Keywords: hodnocení rizik; Female; Age Factors; ženské pohlaví; Global Health; celosvětové zdraví; věkové faktory; lidé; Pulmonary Disease, Chronic Obstructive; Risk Assessment; stupeň závažnosti nemoci; stupnice dopadu nemoci na kvalitu života; Sex Factors; chronická obstrukční plicní nemoc; určení symptomu; směrnice pro lékařskou praxi jako téma; progrese nemoci; Male; Aged; sexuální faktory; Practice Guidelines as Topic; Disease Progression; medicína založená na důkazech; Sickness Impact Profile; lidé středního věku; Symptom Assessment; senioři; mužské pohlaví; Severity of Illness Index; Middle Aged; Evidence-Based Medicine; Humans